PENGARUH IKLIM PSIKOLOGIS TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI PT. SARANA TANI PRATAMA - Tenaya, I Gede Indra; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2019)
Organizational Citizenship Behavior is the behavior of choice which does not become part of formal obligation for an employee, but support the organizational effectively. The purpose of this study is to know the influence of Psychological Climate on Job Satisfaction and Organizational Citizenship Behavior in PT. Sarana Tani Pratama. This study conducted on employees in PT. Sarana Tani Pratama. Sample was taken about 99 employees. The sampling technique with random sampling, data collection was done by distributing questionnaires using Likert scale 5 point to measure 27 items of statement. Analytical technique with path analysis. The result of this study indicate that psychological climate is positive and significant impact to job satisfaction. Secondary, psychological climate is positive and significant impact to organizational behavior. Third, job satisfaction is positive and significant impact to organizational citizenship behavior. The implication that can happen from this study is the company must be creates a good psychological climate so might be creates higher job satisfactory level and the emergence of working environment that be committed to achievement of company goals.